(Re)visualizing national history : museums and national identities in Europe in the new millennium - Ostow, Robin 1945- Herausgeber (German and European studies, 2008)
"(Re) Visualizing National History considers the wave of monument and museum building in Europe as part of an attempt to forge consensus in politically unified but deeply divided nations. This collection explores ways in which museums exhibit emerging national values and how the establishment of these new museums (and new exhibits in older museums) reflects the search for a consensus among different generational groups in Europe and North America. The contributors come from a variety of countries and academic backgrounds, and speak from such varied perspectives as cultural studies, history, anthropology, sociology, and museum studies. (Re)Visualizing National History is an interdisciplinary volume that offers insights on the dilemmas of present-day European culture, manifestations of nationalism in Europe, and the debates surrounding museums as sites for the representation of politics and history."--BOOK JACKET.